A multi-scale model of dislocation plasticity in α-Fe: Incorporating temperature, strain rate and non-Schmid effects. (October 2015) - Lim, H.; Hale, L.M.; Zimmerman, J.A.; Battaile, C.C.; Weinberger, C.R.
Abstract: In this work, we develop an atomistically informed crystal plasticity finite element (CP-FE) model for body-centered-cubic (BCC) α -Fe that incorporates non-Schmid stress dependent slip with temperature and strain rate effects. Based on recent insights obtained from atomistic simulations, we propose a new constitutive model that combines a generalized non-Schmid yield law with aspects from a line tension (LT) model for describing activation enthalpy required for the motion of dislocation kinks. Atomistic calculations are conducted to quantify the non-Schmid effects while both experimental data and atomistic simulations are used to assess the temperature and strain rate effects. The parameterized constitutive equation is implemented into a BCC CP-FE model to simulate plastic deformation of single and polycrystalline Fe which is compared with experimental data from the literature. This direct comparison demonstrates that the atomistically informed model accurately captures the effects of crystal orientation, temperature and strain rate on the flow behavior of siangle crystal Fe. Furthermore, our proposed CP-FE model exhibits temperature and strain rate dependent flow and yield surfaces in polycrystalline Fe that deviate from conventional CP-FE models based on Schmid's law. Highlights: A new crystal plasticity finite element model for bcc iron is proposed. This model is parameterized with atomistic simulation and single crystal experiments. This model incorporates temperature, strain rate and non-Schmid effects. Predictions of yield in iron showed good agreement with experiments. Non-Schmid effects are most significant at low temperatures and high strain rates.